Co-operative Governance Index (Co-opGI) and its application in credit co-operatives in Malaysia / Hayati Md. Salleh - Md. Salleh, Hayati (2011)
This study creates a measure of co-operative governance in the form of co-operative governance index (Co-opGI) based on a dataset from 78 credit co-operatives in Malaysia. Co-opGI is a composite measure of 20 indicators derived from experts' opinion, survey and annual reports under the categories of four co-operative governance mechanisms: board effectiveness, member active participation, internal audit committee's efficiency and management's efficiency. There are five stages of process in constructing the Co-opGI: (i) indicators identification, (ii) measurement identification, (iii) measurement standardisation, (iv) measurement weighting and (v) measurement conversion into indices. This index is used as a proxy measure of the level of co-operative governance in a co-operative. The study relates Co-opGI to co-operative performance and finds no significant relationship. The study examines the relationship of size of co-operative governance organs (members, board, internal audit committee and management) with Co-opGI. The result shows that size of management and size of internal audit committee relate positively with Co-opGI. Cluster analysis groups the 78 co-operatives into five groups according to their levels of Co-opGI and finds that size, competency and compliance of internal audit committee are significantly different across the five groups of Co-opGI in which the Very High Co-opGI group shows the highest scores. The tests show that board communication, member active participation and management efficiency differ significantly between the CoopGI groups. The results imply that Co-opGI is valid and reliable in measuring corporate governance in co-operatives.